Vector‐borne diseases. (11th May 2017) - ,; More, Simon; Bicout, Dominique; Bøtner, Anette; Butterworth, Andrew; Calistri, Paolo; De Koeijer, Aline; Depner, Klaus; Edwards, Sandra; Garin‐Bastuji, Bruno; Good, Margaret; Gortazar Schmidt, Christian; et al.
Abstract: After a request from the European Commission, EFSA's Panel on Animal Health and Welfare summarised the main characteristics of 36 vector‐borne diseases (VBDs) in 36 web-based storymaps . The risk of introduction in the EU through movement of livestock or pets was assessed for each of the 36 VBDs individually, using a semiquantitative Method to INTegrate all relevant RISK aspects (MINTRISK model), which was further modified to a European scale into the EFSA-VBD-RISK-model . Only eight of the 36 VBD‐agents had an overall rate of introduction in the EU (being the combination of the rate of entry, vector transmission and establishment) which was estimated to be above 0.001 introductions per year. These were Crimean‐Congo haemorrhagic fever virus, bluetongue virus, West Nile virus, Schmallenberg virus, Hepatozoon canis, Leishmania infantum, Bunyamwera virus and Highlands J. virus. For these eight diseases, the annual extent of spread was assessed, assuming the implementation of available, authorised prevention and control measures in the EU. Further, the probability of overwintering was assessed, as well as the possible impact of the VBDs on public health, animal health and farm production. For the other 28 VBD‐agents for which the rate of introduction was estimated to be very low, no further assessments were made. Due to the uncertainty related to some parameters used for the risk assessment or the instable or unpredictability disease situation in some of the source regions, it is recommended to update the assessment when new information becomes available. Since this risk assessment was carried out for large regions in the EU for many VBD‐agents, it should be considered as a first screening. If a more detailed risk assessment for a specific VBD is wished for on a national or subnational level, the EFSA‐VBD‐RISK‐model is freely available for this purpose.